Raman microspectroscopy as a useful new tool in understanding thoracic aortic aneurysms - DePaolo, John (Cell Rep Med, 2021)
Raman spectroscopy is a well-understood technology with novel applications in both research and clinical settings. In their article, Sugiyama and colleagues apply this technology to understand thoracic aortic aneurysm development and biomarker identification.(1)